Маркетинг стратегии и тактики во прехранбената индустрија во Р. Македонија наспроти земјите од ЕУ - Кочоска, Маја (Економски факултет, УКИМ, Скопје, 2013)
Hypocrite said: “Let food be thy medicine and medicine be thy food.” However, do consumers know nowadays what they consume and how food contributes to a better life of higher quality? Food production is in expansion. Products of similar quality and characteristics can be found everywhere. Mass production encourages companies from this sector to search newer and more contemporary ways of production. New trends and consuming habits have transformed the whole way of working. Different kinds of researches and a direct communication with consumers can help building a relationship with them, which requires constant devotion, care and attention. Companies, due to the necessity for healthier and more secure food, are required to implement controlling and security systems as standards that certify the quality. In times when the world is facing the challenges of the economic crisis, market positioning and maintaining the position is a real art. Only those companies that have a strong vision, a good marketing strategy and a real plan, can achieve that. This combination enables building a comparative advantage, an own image, a recognitionality, a brand and a high quality. The European Union has imposed the requirements for products security and high quality as an imperative in the whole food industry. Thorough implementation of food security systems offers production of high quality products that follow the scientific and the innovative achievements, and the changes of the consumers’ socio-demographic structure and habits. R. Macedonia follows these changes, but the economic conditions provoke a real obstacle for their full implementation. Still, the trace is clearly indicated and those who want to stay on the market are obliged to struggle and overcome all the barriers. If we want to become a member of EU we ought to make a lot of efforts, we need professionalism, reforms, high quality products, setting standards, innovations, knowledge and a clear strategy with a firmly set goal.
Strategies and tactics used in the Macedonian food industry compared with the ones in EU countries
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Нада Секуловска.
Keywords: food industry, comparative advantage, innovations, standards, quality, strategy